“They should have just talked to me”: educational pathways of youth in residential care – a participatory action research study - Bruidegom, Kiki; Kuiper, Chris; Bramsen, Inge; De Pooter, Amber; Collet, Francis; Dudevszky, Szabinka; Harder, Annemiek (Frontiers in Education, 2025)
IntroductionYouth in residential care (RC) face the highest risk of unfavorable educational outcomes among all out-of-home care (OHC) settings. While some consistent factors are known from previous research, the voices of youth and their caregivers remain largely absent, limiting insight into their unique context and opportunities for meaningful improvement.MethodsThis participatory qualitative study examined the educational pathways of 26 youth (aged 12–21) with RC experience and 7 caregivers. Autobiographical interviews explored participants’ experiences and elicited recommendations for professional practice. Data were analyzed using a Grounded Theory approach. In line with participatory action research (PAR), youth with lived experience contributed as co-researchers throughout the study.ResultsParticipants’ experiences were organized into four key themes: (1) awareness of difficulties and their impact, (2) the need for and lack of perspective, (3) longing to be seen and heard, and (4) personal strengths and perceived support. Regarding recommendations for professionals, youth and caregivers emphasized the importance of being genuinely seen and heard, offering attuned motivational support, enabling youth competencies, and fostering a broader, future-oriented perspective involving caregivers and trusted network figures. A genuine connection between professionals and youth was seen as essential, yet often missing in practice.DiscussionThese findings underscore the need for trauma-informed, youth-centered approaches in RC. Key implications include co-constructing educational pathways with youth promoting autonomy, involving caregivers and trusted network members, and equipping professionals with trauma-informed training. By fostering collaboration and relational continuity, professionals can strengthen both educational engagement and psychosocial well-being among youth in RC.